RANGANATHAN VS GORMAN: TINJAUAN ATAS PERKEMBANGAN FIVE LAWS OF LIBRARY SCIENCES - Mafar, Fiqru (Jurnal Ilmu Budaya, 2011)
Not many studies have been done to focus on figures and their thoughts wich are published in library science. In this writing, the writer will present a comparison on Ranganathan's and Gorman's thoughts dealing with "five laws of library sciences". For Ranganathan, the five laws of library science cover 'book are for use, his or her readers every book, every reader it's books, Save the time of the reader, and the library is a growing organism'. While Gorman, the five laws of library science should undergone changes to 'libraries serve humanity, Respect all forms by which knowledge is communicated, use technology intelligently to enhance service librarians, protect free access to knowledge, and honors the past and create the future'